Review on Management of iron deficiency Anaemia with Ayurveda. - Karande, Shraddha D; Hiremath, S S; Hudedmani, Irappa; Badiger, M S (International Research Journal of Ayurveda & Yoga, 2021)
Introduction- In India, anaemia is a major public health issue. Because all of the clinical signs and symptoms of Pandu and anaemia are similar, the clinical condition of Pandu in Ayurveda can be linked to anaemia as described in mainstream medicine. Apart from the existing platforms, complementary and alternative systems/traditional medications can be investigated for the treatment of anaemia. Aims-To examine numerous Nighantu (dictionaries), Samhita (traditional Ayurvedic treatise), Samgrahagrantha, Chikitsagrantha (Ayurvedic compendia), and Rasagrantha (compendia connected to Rasashastra) to determine the various formulas used for the prevention and management of Panduroga . Material and methods- Classical Ayurvedic books, were thoroughly examined, together with Sanskrit commentary were explored. A thorough search of the Internet was conducted to locate prior study papers and related material to Anaemia. Result and conclusion- Ayurveda the traditional science of Indian medical system described Pandu roga as Pitta Pradana Vyadhi which mainly affects Rasa and Rakta Dhatu. Disease involves lack of Dhatus nourishment due to intake of Pitta Prakopaka Ahara. Various ayurvedic formulations described in Ayurveda if taken appropriately could help in treatment of this disease.